Biotelemetry systems and the design of a low cost microprocessor controlled radiotelemetry system - Çolgar, M. Fatih. (Thesis (M.S.) - Bogazici University. Institute of Biomedical Engineering, 1985., 1985)
In this thesis, Biotelemetry systems are presented in general, with various coding systems that send different physiological signals. After that, a special Biotelemetry system is designed, to demonstrate how different methods are employed to solve problems, and the implementation of different blocks of a Biotelemetry system. As it can be seen on the following pages, the system designed for demonstration has different approaches to some well known subjects.
Keywords: Biotelemetry.; Radio telemetry.